WEAVING MYTHS: THE MYTHOLOGICAL WORLD OF AMISH TRIPATHI - Dr. Suresh P. Agale (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Amish Tripathi, a pioneering Indian author, has reshaped the landscape of Indian literature through his distinctive mythological novels. This paper offers an analytical exploration of Tripathi's literary craft, focusing on his narrative techniques, thematic depth, and cultural contextualization. At the core of Tripathi's work lies narrative innovation, where ancient myths are skillfully reinterpreted. The study examines his storytelling methods, highlighting his use of language, symbolism, and narrative structure that breathe new life into age-old tales. Through nuanced character development, Tripathi humanizes mythological figures, forging a meaningful connection between the ancient and contemporary worlds. The thematic analysis underscores his treatment of complex subjects such as religion, philosophy, morality, and ethics, prompting readers to engage with timeless questions and fostering a nuanced understanding of spirituality and ethical dilemmas. Cultural and historical contexts further enhance Tripathi's storytelling, as his novels bridge temporal divides, transporting readers to ancient India while addressing modern sensibilities. His work enriches the global literary landscape by offering both educational insight and imaginative reinterpretation of Indian mythology. Additionally, the paper considers the contemporary relevance and reception of Tripathi's novels. Garnering global acclaim, his works transcend cultural boundaries, resonating with diverse audiences. Reader responses reveal the emotional and intellectual impact of his mythological narratives, highlighting their universal appeal. In conclusion, Amish Tripathi’s novels exemplify a mythological tapestry that revives ancient narratives while serving as a bridge across cultures. His literary contributions underscore the enduring power of mythology to illuminate human values, inspire reflection, and foster cross-cultural appreciation in the modern literary world.